2009
DOI: 10.1086/597093
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Peripheral CD4+Cell Count Restoration in HIV‐Infected Patients Receiving Long‐Term Antiretroviral Treatment

Abstract: Background Although antiretroviral therapy has the ability to fully restore a normal CD4+ cell count (>500 cells/mm3) in most patients, it is not yet clear whether all patients can achieve normalization of their CD4+ cell count, in part because no study has followed up patients for >7 years. Methods Three hundred sixty-six patients from 5 clinical cohorts who maintained a plasma human immunodeficiency virus (HIV) RNA level ≤1000 copies/mL for at least 4 years after initiation of antiretroviral therapy were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
279
4
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(323 citation statements)
references
References 35 publications
26
279
4
14
Order By: Relevance
“…1,59 We found that the identical clinical parameters were associated with increased rate of CD4 T-cell recovery by using both approaches and were consistent with other observational studies of CD4 T-cell recovery after cART. 2,16 It is important to note however, that this study was designed to replicate our previous study of Caucasians 22 where we had previously used a survival analysis approach.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…1,59 We found that the identical clinical parameters were associated with increased rate of CD4 T-cell recovery by using both approaches and were consistent with other observational studies of CD4 T-cell recovery after cART. 2,16 It is important to note however, that this study was designed to replicate our previous study of Caucasians 22 where we had previously used a survival analysis approach.…”
Section: Discussionsupporting
confidence: 89%
“…[1][2][3] These patients remain at increased risk of non-AIDS-related illnesses and mortality despite years of suppressive cART. [4][5][6] Clinical or genetic factors that may predict impaired CD4 T-cell recovery could potentially be used to identify patients who would benefit from earlier initiation of cART.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…500 mL) after a mean time of 7.5 y on antiretroviral therapy (ART) (1). Persistent depletion of CD4 + T cells in lymphoid tissue, such as gut-associated lymphoid tissue, is even more pronounced than in blood (2).…”
mentioning
confidence: 99%
“…The extent of the damage is related to the length of time of infection (or more appropriately to the nadir of CD4 þ Tcell count). This damage is seen by an inability to completely replace the CD4 þ T-cell compartment after therapy in initiated (Kelley et al 2009), which may be due in part to depletion of the host capacity to generate CD4 þ T cells over time, or to damage of the architecture of the lymphoid tissue that results in reduced capacity to support CD4 þ T-cell function (Lackner et al 2011). …”
Section: Blood and Lymph Nodesmentioning
confidence: 99%